Analysis of Accounting Information Systems and E-Marketing for MSMEs in Pari Village Serdang Bedagai - Noviani; Hernawaty Hernawaty; Sri Wahyuni; Miftahurrahman Sinaga (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Micro, Small and Medium Enterprises (MSMEs) are business sectors that consistently develop in the national economy. This research was conducted on MSME actors in the village of Kota Pari Serdang Bedagai, especially palm sugar business actors. This study aims to analyse accounting information systems and e-marketing for MSMEs in Kota Pari Village, Serdang Bedagai. This type of research is descriptive using a qualitative approach. Data analysis techniques used in this study include observation, interviews, and documentation. The results of this study are that MSMEs in Kota Pari Serdang Bedagai village have not carried out Accounting Information Systems and e-marketing properly. Bookkeeping records still use notebooks whose contents are only receipts and expenses. Marketing of brown sugar in MSMEs in Kota Pari village Serdang Bedagai has also not used an e-marketing system. Marketing of brown sugar products generally still runs traditionally, namely by word of mouth, the marketing channels carried out are only from producers to collector traders. Their obstacle is the lack of knowledge about e-marketing due to the level of education and lack of socialisation about the e-marketing system. From the results of research and discussion, it is known that the level of education affects the use of accounting information systems and e-marketing.